Complementarities between policy actions in software production in emerging economies. The case of Argentina - Motta, Jorge; Morero, Hernán Alejandro; Borrastero, Carina; Ortiz, Pablo Arnaldo (2021)
Fil: Motta, Jorge. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.